Os Mega-acordos comerciais e suas redes de acordos prévios: Análise comparativa com temas regulados pelos acordos prévios e pela OMC - Marina Amaral Egydio de Carvalho; Marcus Maurerde Salles (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This discussion work identifies which are the agreements previously concluded by the member countries of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), the Regional Comprehensive Economic Partnership (RCEP) and the African Continental Free Trade Area (AfCFTA). In addition, the work compares the rules provided for in these agreements with the mega trade agreements, as well as identifies which of these rules are also regulated by the World Trade Organization (WTO) and from the topics established therein which the WTO has not regulated so far.
10419/284911
Keywords: K33; F13; F15; F53; 330; mega-trade agreements; CPTPP; RCEP; AfCFTA; WTO